The Prospect of Mass Customisation in the Chinese Automotive Industry - Dong, Xihan (2011)
The automotive industry is one of the largest manufacturing industries and the development of a country’s automotive industry can represent its economy to some extent. Because of the fierce competition in the automotive industry, customers have more choices and they cannot be satisfied with standard products any more. Therefore, some global automotive manufacturers implement mass customisation as their production strategy which aims to provide customised automobiles according to customers’ requirements. It is reported that China has become the largest automobile market since 2009, which means the automotive manufacturers are facing a large number of demand in the Chinese market. Therefore, it is essential to research the needs of the Chinese customers and their demand for mass customisation, as well as their readiness to the strategy. In addition, since technology of the Chinese automotive industry is comparatively backward, it is necessary to analyse the gaps between the demand of customers and the supply of dealer and manufacturers in order to improve the Chinese automotive industry in the future.